Prevalence and Characterization of Shiga Toxin-Producing and Enteropathogenic Escherichia coli in Shellfish-Harvesting Areas and Their Watersheds - Balière, Charlotte; Rincé, Alain; Blanco, Jorge; Dahbi, Ghizlane; Harel, Josée; Vogeleer, Philippe; Giard, Jean-Christophe; Mariani-Kurkdjian, Patricia; Gourmelon, Michèle (Frontiers in Microbiology, 2015)
During a two-year study, the presence of Shiga-toxin producing E. coli (STEC) and enteropathogenic E. coli (EPEC) was investigated in shellfish (n=238), seawater (n=12) and surface sediment (n=39) collected from three French coastal shellfish-harvesting areas and freshwaters (n=216) in their watersheds. PCR detection of Shiga toxin- (stx1/stx2) and intimin- (eae) genes following enrichment from these samples revealed the presence of least one of the stx genes in 30.3% of shellfish batches, 85.9% of freshwater, 41.7% of seawater, and 28.2% of sediment samples, while the eae gene was observed in 74.8%, 100%, 100%, and 43.6% of shellfish batches, freshwater, seawater, and sediment samples, respectively. Twenty-eight STEC and 89 EPEC strains were isolated and analyzed in order to determine their serotype, phylogroup, and genetic relatedness and to evaluate the presence of the saa and ehxA genes encoding the STEC autoagglutinating adhesin and the enterohemolysin A, respectively. Finally, the ability to form biofilms and antimicrobial susceptibility were investigated for a selection of strains. Eighteen serotypes were identified among the STEC isolates and 57 among the EPEC isolates. A high diversity was observed within these strains, as 79 different PFGE patterns and 48 distinguishable sequence types were identified. Strains were found to belong mainly to phylogroups B1 and B2 and virulence was observed to be low as more than 85% of the strains possessed only stx1, stx2 or eae genes. One STEC and several EPEC strains belonged to three of the five highly pathogenic serogroups (i.e., O26, O103, and O145). The subset of strains tested for their capacity to form biofilms was mainly strongly to moderately adherent and more strains formed a strong biofilm at 18°C than at 30°C. Finally, more than 85% of analyzed strains were found to be sensitive to the 16 tested antibiotics. These data suggest the low risk of human infection by STEC if shellfish from these shellfish-harvesting areas were consumed.